Randomized Trial of Patiromer on Efficacy to Reduce Episodic Hyperkalemia in Patients with ESKD Treated With Hemodialysis - John P. Middleton; Shifeng Sun; Susan Murray; Clemontina A. Davenport; James P. Daubert (Kidney International Reports)
Introduction: Individuals with end-stage kidney disease (ESKD) maintained on hemodialysis (HD) carry a high risk of cardiac arrhythmias. This risk is heightened by episodic hyperkalemia. The purpose of the study was to investigate whether patiromer administered daily reduced episodes of hyperkalemia in those with ESKD who receive HD, and to explore whether prescription of patiromer reduced the number of significant arrhythmia events. Methods: This was a prospective, randomized, open-label trial. Eligible patients with ESKD on HD were identified. Participants were randomized 1:1 to patiromer versus usual care. Those randomized to patiromer were administered the medication daily, and the dose was titrated based on serum potassium concentrations at the start of weeks 1, 2, and 3. All participants received 7-day continuous cardiac monitors at baseline and at week 4. Results: Of the 33 participants who were randomized, 1 withdrew due to adverse symptoms, and 1 withdrew due to pregnancy, leaving 31 in our analytic cohort. The mean age of randomized participants was 56 years, 55% were male, 81% were Black, and 10% were Hispanic/Latino. In week 4, the number of episodes of serum potassium ≥ 5.5 mEq/l was 13 in the patiromer group and 41 in the control group; with median number of episodes of hyperkalemia in the patiromer group significantly lower than that of control group (0 vs. 3, P = 0.024). In week 4 continuous cardiac monitors, 6 participants had > 1000/24 h premature ventricular contractions, 5 had no sustained ventricular tachycardia (VT), 3 had atrial fibrillation, and 1 had bradycardia, with no significant differences between the groups. Conclusion: Patiromer administered daily reduced the frequency of hyperkalemia in study participants with ESKD who receive thrice-weekly HD. Larger studies are needed to determine whether patiromer reduces significant cardiac events.